2014
DOI: 10.4049/jimmunol.1302525
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA Guanine Nucleotide Exchange Factor, LARG, Mediates ICAM-1–Dependent Mechanotransduction in Endothelial Cells To Stimulate Transendothelial Migration

Abstract: RhoA-mediated cytoskeletal rearrangements in endothelial cells (ECs) play an active role in leukocyte transendothelial cell migration (TEM), a normal physiological process in which leukocytes cross the endothelium to enter the underlying tissue. While much has been learned about RhoA signaling pathways downstream from ICAM-1 in ECs, little is known about the consequences of the tractional forces that leukocytes generate on ECs as they migrate over the surface before TEM. We have found that after applying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 60 publications
2
59
0
Order By: Relevance
“…Interestingly, upon mechanical tension both proteins have been reported to induce RhoA activity. 96,97 In support of a prominent role for ICAM-1, our data show that depletion of ICAM-1 in TNF-a-stimulated endothelial cells resulted in an increase of neutrophil-induced dextran leakage compared to control endothelial cells, although the levels did not reach the levels when RhoA was silenced. 93 PECAM-1 however appeared not to be involved in maintenance of barrier function, as depletion in ECs had no effect on neutrophilinduced dextran leakage and neutrophil transmigration numbers.…”
Section: Actin Regulation During Leukocyte Temsupporting
confidence: 61%
“…Interestingly, upon mechanical tension both proteins have been reported to induce RhoA activity. 96,97 In support of a prominent role for ICAM-1, our data show that depletion of ICAM-1 in TNF-a-stimulated endothelial cells resulted in an increase of neutrophil-induced dextran leakage compared to control endothelial cells, although the levels did not reach the levels when RhoA was silenced. 93 PECAM-1 however appeared not to be involved in maintenance of barrier function, as depletion in ECs had no effect on neutrophilinduced dextran leakage and neutrophil transmigration numbers.…”
Section: Actin Regulation During Leukocyte Temsupporting
confidence: 61%
“…Durotaxis requires the sensing of substrate stiffness by adhesion molecule tugging. 74 The identification of podoprints or adhesive filopodia to probe the EC surface, [75][76][77] together with the recent results obtained by pulling on intercellular adhesion molecule-1 (ICAM-1) using magnetic tweezers 78 certainly support a model of leukocyte-mediated tugging to sense and regulate local EC stiffness.…”
Section: Cross Talk Between Ec Stiffness and Leukocyte Behaviormentioning
confidence: 99%
“…59 In agreement with this, repetitive pulling on adherent anti-ICAM-1-coated magnetic beads using magnetic tweezers increased local EC stiffness. 78 This stiffening response was accompanied by Rho activation and sensitive to inhibitors of actomyosin-based contractility and Rho kinase. The authors identified the RhoGEF LARG (RhoGEF12) as a key upstream activator of Rho.…”
mentioning
confidence: 99%
“…α-actinin-4), increased formation of F-actin stress fibers, RhoA activity and ROCK-myosin-based contraction forces (Heemskerk et al, 2014). ICAM1 clustering induces force-dependent positive feedback-signaling in inflamed ECs, resulting in the amplification of ICAM1 signaling towards the F-actin cytoskeleton and improved leukocyte adhesion (Lessey-Morillon et al, 2014;Schaefer et al, 2014). Accordingly, the application of tension on ICAM1 in order to mimic leukocyte pulling forces further promotes RhoA activity, myosin-based contractile forces and EC stiffening (Fig.…”
Section: Box 1 Mechanotransduction In Inflammatory Diseasementioning
confidence: 99%